Grain Structure Engineering of NiTi Shape Memory Alloys by Intensive Plastic Deformation - Wang, Zifan; Chen, Jingwei; Kocich, Radim; Tardif, Samuel; Dolbnya, Igor P; Kunčická, Lenka; Micha, Jean-Sébastien; Liogas, Konstantinos; Magdysyuk, Oxana V; Szurman, Ivo; Korsunsky, Alexander M (ACS applied materials & interfaces, 2022)
To explore an effective route of customizing the superelasticity (SE) of NiTi shape memory alloys via modifying the grain structure, binary Ni55Ti45 (wt) alloys were fabricated in as-cast, hot swaged, and hot-rolled conditions, presenting contrasting grain sizes and grain boundary types. In situ synchrotron X-ray Laue microdiffraction and in situ synchrotron X-ray powder diffraction techniques were employed to unravel the underlying grain structure mechanisms that cause the diversity of SE performance among the three materials. The evolution of lattice rotation, strain field, and phase transformation has been revealed at the micro- and mesoscale, and the effect of grain structure on SE performance has been quantified. It was found that (i) the Ni4Ti3 and NiTi2 precipitates are similar among the three materials in terms of morphology, size, and orientation distribution; (ii) phase transformation happens preferentially near high-angle grain boundary (HAGB) yet randomly in low-angle grain boundary (LAGB) structures; (iii) the smaller the grain size, the higher the phase transformation nucleation kinetics, and the lower the propagation kinetics; (iv) stress concentration happens near HAGBs, while no obvious stress concentration can be observed in the LAGB grain structure during loading; (v) the statistical distribution of strain in the three materials becomes asymmetric during loading; (vi) three grain lattice rotation modes are identified and termed for the first time, namely, multi-extension rotation, rigid rotation, and nondispersive rotation; and (vii) the texture evolution of B2 austenite and B19' martensite is not strongly dependent on the grain structure.
Keywords: multiscale; grain structure; lattice rotation; powder diffraction; bespoke NiTi shape memory alloys; Laue microdiffraction; phase transformation